Misunderstanding, conflict and divisions between the Visegrad Group and the European Union: an analytical discourse beyond the public cliche of the migration crisis - Birgit Schmölz (CES Working Papers, 2019)
The current connection between the European Union (EU) and the Visegrad group (V4) seems to resemble a parent-child relation: the perception of a dictating European Commission, on the one hand, and a rather stubborn driven behaviour on part of the Visegrad players, on the other hand, is undeniable. Certainly, the migration crisis was a crucial issue for both sides and it definitely destabilised the harmony balance between the EU and the Central Eastern European (CEE) states. Hence, the question raised is whether there are more fundamental reasons behind the phenomena of a highly tensed environment. This paper strives for an explanation on the self-perceived role of the Visegrad format and the perception of the "other" within the European Union.
Keywords: 330; Visegrad Group; European polycrisis; role concept; identity concept